2015
DOI: 10.1136/bmjopen-2014-007231
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of alprazolam in allostatic load and neurocognition of patients with anxiety disorders and chronic stress (GEMA): observational study protocol

Abstract: IntroductionThe allostatic load model explains the additive effects of multiple biological processes that accelerate pathophysiology related to stress, particularly in the central nervous system. Stress-related mental conditions such as anxiety disorders and neuroticism (a well-known stress vulnerability factor), have been linked to disturbances of hypothalamo–pituitary–adrenal with cognitive implications. Nevertheless, there are controversial results in the literature and there is a need to determine the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…This model supports recent findings from our group (Sieberg et al, 2018). We examined the effects of lifelong mild stress on levels of neuropathic pain and the effects of chronic neuropathic injury on anxiety-like behavior in mice with results demonstrating a strong link between chronic neuropathic pain and chronic anxiety (Soria et al, 2015), with the driver of this comorbidity being neuropathic pain as opposed to ongoing stress (Sieberg et al, 2018). However, the timing, severity, and type of stress needed to induce this cruel cycle is unclear, and alternatively, if there is a healthy or protective dose of stress that could buffer or prevent the onset of chronic pain, or how much stress is protective is also unknown.…”
Section: Link Between Chronic Pain and Stresssupporting
confidence: 87%
“…This model supports recent findings from our group (Sieberg et al, 2018). We examined the effects of lifelong mild stress on levels of neuropathic pain and the effects of chronic neuropathic injury on anxiety-like behavior in mice with results demonstrating a strong link between chronic neuropathic pain and chronic anxiety (Soria et al, 2015), with the driver of this comorbidity being neuropathic pain as opposed to ongoing stress (Sieberg et al, 2018). However, the timing, severity, and type of stress needed to induce this cruel cycle is unclear, and alternatively, if there is a healthy or protective dose of stress that could buffer or prevent the onset of chronic pain, or how much stress is protective is also unknown.…”
Section: Link Between Chronic Pain and Stresssupporting
confidence: 87%
“…Controlled studies will be performed in the coming steps and different goals. In this study we did not report the cognitive variables (described in the original protocol and still under analysis) [27], which are planned for future evaluation. Furthermore, as a significant reduction in the total AL index was observed and many AL variables were significantly reduced after treatment, in this open study other non-pharmacological factors may also be considered to be interacting during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This report is part of the preliminary results of the GEMA study protocol, which has been discussed in detail in a previous publication [27]. In this open and prospective study volunteer patients were recruited since September 2011 until May 2014, after signing the informed consent.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of the outpatients' use of benzodiazepines has been increased substantially in the last years, especially among clinicians, psychiatrists and neurologists [20]; indeed clinical studies are continually needed to determine safety in long term uses. The GEMA project (Gador Study of Stress Modulation by Alprazolam) [21] consists of a series of consecutive studies performed on a group of high symptomatic outpatients with general anxiety disorder (GAD) 2 associated with chronic stress, determined by high allostatic load (AL) levels (indicators for the functioning of the main potentially stress affected systems) [22] [23] and neuroticism (a clinical condition well-known as a stress vulnerability factor and defined as an exaggerated response to psychosocial stressors with intense emotional reaction) [ In a previous analysis performed by our group in the same cohort of patients, we analyzed the AL index and determined the effects of sex and age on allostatic load variables before and after treatment [28]. In this study we found that female sex was associated with higher levels of anxiety with a better profile in the same allostatic load variables such as cardiovascular ones.…”
Section: Introductionmentioning
confidence: 99%